Purification and characterization of recombinant lipase from Arthrobacter sp. 3B - Padrilah, Siti Nadzirah (2015)
A recombinant lipase from Arthrobacter sp. 3B, was successfully purified and characterized. The lipase was purified using affinity chromatography with Nickel sepharose as a resin. The molecular weight of the pure protein was estimated to be 66.2 kDa by SDS-PAGE. The enzyme exhibited maximum activity at 60ᵒC and was stable at the temperature lower than 60ᵒC. The enzyme indicated that the optimum pH for the enzyme activity and stability was pH 7. Lipase 3B has broad substrate specificity, which tend to hydrolyze most natural oils that contain medium and long chain fatty acid, with the highest activity in canola oil (C18:1). Lipase activity was enhanced in the presence of metal ions, especially K⁺, Ca²⁺, and Mg²⁺ ions in 1 mM concentration, but it was inhibited by Ni²⁺ ion. The activity of the purified enzyme was slightly decreased in the present of organic solvents. These properties suggest that the lipase may find potential applications in industrial and biotechnology applications.